Answer:
It's 13
Step-by-step explanation:
Well, just use the triangle inequality theorem and pay close attention to angles CAB and EAC... that's all I can say
Hope that helped
Given the functions
(a) f(x) = x³ + 5x² + x
(b) f(x) = x² + x
(c) f(x) = -x
Function (a)
f(-x) = (-x)³ + 5(-x)² + (-x)
= -x³ + 5x² - x
= -(x³ - 5x² + x)
The function is neither even nor odd.
Function (b)
f(-x) = (-x)² + (-x)
= -(-x² + x)
The function is neither even nor odd.
Function (c)
f(-x) = -(-x)
= x
= -f(x)
Because f(-x) = -f(x) the function is odd.
Answer: f(x) = -x is an odd function.
Just took the test. A is the right answer.
Answer: median
Step-by-step explanation:
Answer:
quadratic
Step-by-step explanation: